2018
DOI: 10.1016/j.neubiorev.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Treatment resistant depression: A multi-scale, systems biology approach

Abstract: An estimated 50% of depressed patients are inadequately treated by available interventions. Even with an eventual recovery, many patients require a trial and error approach, as there are no reliable guidelines to match patients to optimal treatments and many patients develop treatment resistance over time. This situation derives from the heterogeneity of depression and the lack of biomarkers for stratification by distinct depression subtypes. There is thus a dire need for novel therapies. To address these know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
236
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 363 publications
(243 citation statements)
references
References 214 publications
(248 reference statements)
4
236
0
3
Order By: Relevance
“…The amygdala is strongly implicated in human depression (3032), and the profound effects we observed in the amygdala are likely due to the chronic condition of the disorder. In contrast, animal models tend to measure spontaneous, acute depression-like behavior in which the hippocampus appears to be the relevant brain area (33). We then performed a microarray study in the dentate gyrus and found increased CTGF expression in bLRs that exhibit increased anxiety-like and depression-like behavior compared with bHRs.…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala is strongly implicated in human depression (3032), and the profound effects we observed in the amygdala are likely due to the chronic condition of the disorder. In contrast, animal models tend to measure spontaneous, acute depression-like behavior in which the hippocampus appears to be the relevant brain area (33). We then performed a microarray study in the dentate gyrus and found increased CTGF expression in bLRs that exhibit increased anxiety-like and depression-like behavior compared with bHRs.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, 714 this heterogeneity can be used to generate diverse groups of mice after an insult, e.g. mice 715 30 susceptible and resilient to depression thus mimicking human conditions (Akil et al, 2018). 716…”
Section: Discussion 666mentioning
confidence: 99%
“…Major depressive disorder is the most common neuropsychiatric disease, characterized by the persistence of negative mood and loss of pleasure. It has surpassed heart diseases and cancer to become the leading cause of disability worldwide, affecting more than 320 million people, with a rapid increase of prevalence between 2005 and 2015 . The current severe status of depression urgently demands more efficient antidepressant drugs, as traditional antidepressants are associated with delayed therapeutic responses, along with low responsive and remissive rates among patients with depression …”
Section: Introductionmentioning
confidence: 99%
“…It has surpassed heart diseases and cancer to become the leading cause of disability worldwide, 1,2 affecting more than 320 million people, with a rapid increase of prevalence between 2005 and 2015. 3 The current severe status of depression urgently demands more efficient antidepressant drugs, as traditional antidepressants are associated with delayed therapeutic responses, along with low responsive and remissive rates among patients with depression. 4,5 Accumulated evidence has shown that Xiaoyaosan, a traditional Chinese herbal formula, exerts antidepressant effects via improving the core symptoms of behavioral despair and anhedonia.…”
Section: Introductionmentioning
confidence: 99%